Intensive Glucose Control Reduces the Risk Effect of TRIB3, SMARCD3, and ATF6 Genetic Variation on Diabetic Vascular Complications - He, Fazhong; Shu, Yan; Wang, Xingyu; Liu, Xin; Liu, Guojing; Chen, Zhangren; Wang, Zhenmin; Li, Ling; Liu, Rong; Zhou, Honghao; Xu, Heng; Zhang, Wei; et al. (Frontiers in Pharmacology, 2018)
Type 2 diabetes mellitus is a complex disease. Our previous study revealed that TRIB3 genetic variations were strongly associated with diabetic vascular complications, although TRIB3 regulation pathways remain poorly understood. We used two extreme treatment groups from a 2×2 factorial randomized controlled trial to identify a positive association, which was further validated in patients receiving cross treatment to test the effect of genetic polymorphisms among the different treatment groups. A gene-centric score (GS)-weighted model including the three associated genetic variations TRIB3 rs2295490, ATF6 rs12086247, and SMARCD3 rs58125572 was used. The results of the GS model indicated a 46% reduction in the risk of primary vascular complications in patients bearing more than two risk alleles (hazard ratio (HR) 0.54, 95% confidence interval (CI) 0.38-0.76, p < 0.001), following intensive glucose control treatment when compared with patients who received standard glucose control treatment. Furthermore, these patients benefited from active blood pressure-lowering treatment (HR 0.39, 95% CI 0.24-0.64, p < 0.001). However, no significant difference was observed between the two interventions in patients with fewer than two risk alleles (HR 1.09, 95% CI 0.86-1.39, p = 0.47). These results indicate that genetic variants in these three genes may be useful biomarkers for individualized drug therapy in diabetic patients.